Beyond the device and the triple identity: the new limits of res judicata res judicata and the impossibility of a new claim based on the same grounds already already known and appreciated (Revista do Tribunal Regional Federal da 3ª Região, 2016)
The purpose of this essay is to address the objective limits of res judicata, showing how legal certainty requires that immutability also be extended to certain aspects of the grounds, otherwise the mere modification of the claim in a second lawsuit could prove to be capable of defrauding the outcome of the previous case. Thus, the aim is to draw up a definition that promotes, in practice, respect for the principles of access to justice, adversarial proceedings, a broad defense and the reasoning behind judicial decisions, without circumventing what has already been established in a previous judgment, respecting res judicata and repudiating attempts to defraud it. To this end, we begin by demonstrating the insufficiency of the triple identity criterion, go through doctrinal and jurisprudential contributions and end up analyzing the new and promising legal regime given to the issue of the objective limits of res judicata in the New Code of Civil Procedure (NCPC).
Keywords: res judicata×limits×triple identity×fundamentals already considered×NCPC×; res judicata; limits; triple identity; fundamentals already considered; NCPC